Breaking Barriers: Addressing STI Healthcare Access Challenges among Rohingya Refugees in Bangladesh (IAHS Medical Journal, 2024)
Background: The Rohingya refugee crisis, stemming from Myanmar's Rakhine State, has led to a significant displacement of nearly a million Rohingya seeking refuge in Bangladesh's Cox's Bazar district. Among the myriad health challenges faced by this population, Sexually Transmitted Infections (STIs) present a pressing concern. The study aimed to explore the burden of STIs among Rohingya refugees in Cox's Bazar, Bangladesh, by examining the prevalence of STIs, associated risk factors and access to healthcare services.Materials and methods: A cross-sectional study was conducted from January to December 2023, involving 150 Rohingya refugees residing in refugee camps in Cox's Bazar. Data collection included demographic characteristics, STI symptoms, healthcare-seeking behavior, perceived barriers to healthcare access and access to transportation.Descriptive statistics, bivariate correlation analysis and logistic regression were employed for data analysis.Results: Preliminary findings revealed a high prevalence of STI symptoms among Rohingya refugees, with 20.0% experiencing genital ulcers, 33.3% reporting vaginal discharge and 26.7% suffering from painful urination. However, only 46.7% sought treatment from healthcare providers, with perceived barriers such as financial constraints (40.0%) and lack of awareness (26.7%) hindering access to healthcare.Conclusion: By shedding light on the complex interplay of demographic, socioeconomic and healthcare-related factors, this study contributes to a deeper understanding of the health challenges faced by displaced populations and underscores the importance of tailored healthcare strategies in humanitarian settings.IAHS Medical Journal Vol 7(1), June 2024; 32-34